Novedades en Huperzia Bernh. (Lycopodiaceae) de Costa Rica - Rojas Alvarado, Alexander Francisco (Lankesteriana: International Journal on Orchidology, 2015)
ONE NEW SPECIES AND TWO NEW RECORDS OF Huperzia (Lycopodiaceae) from Costa Rica are included here. The new species, H. oellgaardii A.Rojas is compared to H. taxifolia (Sw.) Trevis. and differs by subdimorphic leaves (vs. monomorphic), sterile leaves 2.5-3.5 mm wide (vs. 1.5-2.5 mm wide), fertile leaves 1.5-3.0 mm wide [vs. 1.0-1.5 (-2.0) mm wide] and distribution (1800-2900 m vs. 600-2300 m). H. chiricana (Maxon) Holub was collected in Volcán Turrialba and H. lancifolia (Maxon) Holub in Jicotea of Turrialba and Cerro Pittier of Coto Brus, Costa Rica.